Assessing a Method of Mechanical Cervical Dislocation as a Humane Option for On-Farm Killing Using Anesthetized Poults and Young Turkeys - Woolcott, Caitlin R.; Torrey, Stephanie; Turner, Patricia V.; Chalmers, Heather; Levison, Lena J.; Schwean-Lardner, Karen; Widowski, Tina M. (Frontiers in Veterinary Science, 2018)
Our objective was to determine the efficacy of manual cervical dislocation versus a mechanical cervical dislocation device for on-farm killing of poults and young turkeys. Forty-two 1- and 3-week old turkeys were randomly assigned to one of three experimental groups: awake manual cervical dislocation (CD), anesthetized manual cervical dislocation (aCD) or anesthetized mechanical cervical dislocation (MCD). Anesthetized birds received an intramuscular dose of 0.3 mg/kg medetomidine and 30 mg/kg of ketamine to achieve a light plane of anesthesia. A comparison of CD versus aCD responses indicated that the anesthetic plane did not affect jaw tone or pupillary light reflex, indicators of loss of sensibility and brain death, respectively. MCD was unsuccessful for killing 1-week old poults as indicated by the ongoing presence of the pupillary eye reflex as well as failure to achieve cardiac arrest within 5 minutes in 5 of 5 birds. Radiographs also indicated no vertebral dislocation or fracture. Pupillary light reflex was present in 98% and jaw tone was present in 73% of turkeys, respectively, for all groups combined, but retention of the pupillary light reflex (P<0.001) and jaw tone (P=0.001) was longer for birds killed by MCD. Time to last movement (P=0.797) and cardiac arrest (P=0.057) did not differ between method. Survey radiographs demonstrated an effect of method for the average displacement distance at the site of vertebral dislocation, with a greater distance observed in birds killed by CD compared to MCD (P=0.003). A method by age interaction was observed between CD and MCD for the number of birds with fractures; more vertebral fractures were observed in 3-week old turkeys killed with MCD compared to CD (P=0.047). Upon gross examination, the majority of birds killed by either method had minimal to no hemorrhage within the brain and spinal cord. However, turkeys killed using CD had more microscopic subdural brain hemorrhage (P=0.020). Ante-mortem and post-mortem measures suggest that neither manual CD nor the MCD tool used in this study caused immediate insensibility, but CD resulted in a shorter latency to brain death and fewer fractures compared to MCD.